Do information differentials and confidence in medical institutions influence out-of-pocket expenditure on health care in India? - Deepabali Bhattacharjee; Pratap C. Mohanty (Elsevier, 2022)
Background: This paper identifies the factors responsible for higher out-of-pocket expenditure on healthcare in India with a focus on confidence in medical institutions and information differentials in the health care sector. Design/methodology/ approach: The analysis is based on IHDS-I (2004-05) and IHDS-II (2011-12) database by applying the log-linear regression method to find out the impact of different independent variables on OOPE (dependent variable). An information index is made using the information related variables available in IHDS dataset by applying the Principal Component Analysis method. Results: Findings identify that the factors like location, education, age and caste of the respondents play a significant role in determining the out-of-pocket expenditure on health care in India. Further, information differentials and confidence in medical institutions among individuals also play an important role. Conclusion: Findings suggest policy-based interventions specifically on better dissemination of Information through ICT pertaining to health care. This also prompts for appropriate regulation by Government on hospitals so that confidence among patients as well as information dissemination will be improved, along with a decline in out-of-pocket expenditure on health care.